2019
DOI: 10.1016/j.geoderma.2019.02.033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of land use change on soil fertility parameters in densely populated areas of Kenya

Abstract: The current study seeks to assess sustainability of agricultural land use by identifying the effect of land use change on soil quality using cross-sectional data collected through a household survey among 525 farm households in densely populated areas of Kenya. Soil samples were collected, analyzed and compared across three land use types: undisturbed, semi-disturbed and cultivated. To achieve these objectives, descriptive, Nutrient Index approach and Classification and Regression Tree (CART) analysis methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 20 publications
7
41
0
Order By: Relevance
“…Our results showed that the highest value of BFI was obtained from grass-covered vineyard. It has been previously reported that soil fertility is proportional to the soil microbial activity and SOM, as well as altering environmental conditions and land uses [47,48]. It has also been proved that crop residues and cover crops increase soil microbial biomass and activity and improve SOC sequestration in the long-term [49].…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed that the highest value of BFI was obtained from grass-covered vineyard. It has been previously reported that soil fertility is proportional to the soil microbial activity and SOM, as well as altering environmental conditions and land uses [47,48]. It has also been proved that crop residues and cover crops increase soil microbial biomass and activity and improve SOC sequestration in the long-term [49].…”
Section: Discussionmentioning
confidence: 97%
“…It is obvious, based on results from studies by Chinese and foreign academics, that foreign academics place more of their focus on the effects that tillage [27], cultivation [28], stakeholders' knowledge [29], biofuels [30], and sustainable development ideas [31] have on sustainable land utilization behaviors than on problems with China's present land policy. While Chinese academics have noted that economic factors such as unsound contracts, high risk of breach of contract, and the instability of management rights are primary reasons behind the use of short-term contracts and short-term behaviors in land trusteeship in China, no effective contract system has yet been developed.…”
Section: Current Researchmentioning
confidence: 99%
“…While, nutrient index for salt index (2.09) and exchangeable Ca (2.27) were medium; these data indicate to that the soil fertility status was medium according to EC and exchangeable Ca. Additionally, soil fertility status was high according to nutrient index of these parameters as following: soil reaction index (3.00), organic matter (2.45), available P (2.45), available K (2.913), CEC (2.45), C/N ratio (2.36), exchangeable K (2.64), exchangeable Na (2.45) and exchangeable Mg (2.91), (Verma et al, 2005;Abah and Petja, 2015;Willy et al, 2019 andEl-Seedy, 2019). Table 7.…”
Section: Nutrient Index (Ni) Of Soil Propertiesmentioning
confidence: 99%
“…A nutrient index (NI) of soil properties is distribution estimate percent of soil samples through three classes: high, medium and low of nutrient status (Willy et al, 2019). Nutrient index can be used as a guide and indication on soil fertility status (organic carbon, available phosphorus, available potassium and soil reaction index).…”
Section: Introductionmentioning
confidence: 99%